(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
YouTube, Instagram and TikTok are increasingly used today as tools of resistance and environments of expression. This paper will focus on feminist video-selfies that address stereotypes of the female body, status and behaviour and propose to ironically dismantle them. The article will consider issues of female networked presence and creativity by referring to early attempts to create a personal video channel, documented by Elisa Giardina Papa in her video artwork need ideas!?!PLZ!! (2011). The undercover presentation of political content will be discussed as an activist strategy, as in artist Addie Wagenknecht’s fake make-up tutorials, in which she actually gives instructions on how to protect oneself both online and offline. Video-selfies are widely shared on social platforms as a playful way to meditate on personal identity. This happens, for example, thanks to the social filters of the artist S()fia Braga, which allow users to freely experiment with unfathomable views of themselves and to interact with others in a performative way. All these examples use creative strategies to convey a critical message. While never discouraging physical protest, they offer another ground for activism and dissent, and the possibility of literally embodying them.